Evaluating the U.K.'s Choice of Entry Rate into the ERM. - Wren-Lewis, S (1991)
The paper discusses how a country should choose the rate at which it enters a fixed or quasi-fixed exchange rate zone. It is argued that entry must be consistent with the economy's fundamental equilibrium exchange rate, but that governments can influence the speed of convergence to the fundamental equilibrium exchange rate. Once entry has occurred, this can either involve using fiscal policy to alter the economy's transitional inflation path or monetary policy to move within the currency band. This framework is applied to U.K. entry into the European Monetary System and suggests that entry was at an unrealistically high rate.